O processo de desenvolvimento do professor no contexto do uso das drogas na fase da adolescência - Dias, Eldi Francisco (2015)
Worldwide, drugs have become a serious public health concern. Adolescence is most often the life stage in which the first contact with drugs occurs, due to the fact that this is a period when they face situations of great vulnerability, such as violence, social misfit and risky behavior regarding sexually transmitted diseases and pregnancy, in addition to curiosity and drug trying. As most teenagers are in the school context, the school is considered a privileged space for the development of educational work on the theme of drugs. The aim of this study was to describe the teacher’s development process in the context of drug use in adolescence. This is a Research-Action qualitative study performed with teachers from a school of basic education located in Goiânia - Goiás, which results were analyzed through the Content Analysis method, with a total of 7 (seven) meetings. The speech analysis of the subjects showed three categories: "teachers", "teenagers" and "the role of school and teachers on drug abuse prevention"; and seven subcategories: "the first perceptions of teachers about the theme", "discussing concepts and knowledge of teachers on drugs", "reflecting on the use of drugs", "adolescence and drug use", " prevention of drug use in adolescence", "getting to know the flow of health care for the adolescent taking drugs: the role of school and teacher in the prevention ", as well as " proposal to prevent drug abuse in the school context”. The outcomes showed that teachers' knowledge about drugs is still based on common sense, there is no definition of the role of both school and teacher in the prevention of drug use. Some difficult and demotivating factors like excessive workload, low wages, and the fear of making any intervention related to drug use. The majority of teachers is unaware of the public policies of assistance to teenagers who take drugs and considers that, without some family help, they cannot succeed on approaches with teenagers taking drugs. Even within this context we were able to spark the interest of teachers in building, along with the school, grants to fight the problem of drug use. We proposed to the group of teachers to have some time for discussion, seeking help and partnerships within the healthcare area through the Family Health Strategy and education especially with the university for the implementation of the Health Program at the School, with extension and research activities, and mainly, continuing education for teachers.